Impingement behaviour of single ethanol droplet on a liquid film of glycerol solution. (15th September 2020) - Lu, Lili; Pei, Yiqiang; Qin, Jing; Peng, Zhijun; Wang, Yuqian; Zhu, Qingyang
Abstract: Research on single drop impact, especially in the past two decades, has been motivated by a need for better predictive capability in many industries. However, there are few reports in the literature describing the case of single droplet impinging on liquid films with different physicochemical properties. In this study, laser-induced fluorescence (LIF) methods were used to clarify the impingement behaviour of millimetre-sized single ethanol droplets onto films of different concentrations of glycerol solution. The impingement behaviour is found to differ depending on the Weber number of the incident droplet and the viscosity and the thickness of the liquid film. New results on coalescence/splash thresholds criteria are obtained taking into account the incident droplet Weber number and liquid film characteristics. In addition, the formation mechanism and composition of secondary droplets and crown structures after collision are analysed. For the crown structure parameters, we found that the evolution of the crown height over time is affected by the combination of droplet and liquid film characteristics. The maximum height and diameter of the crown are proportional to the Weber number of the incident droplet, and these parameters can be predicted by the combination of the incident droplet Weber number and the liquid film Ohnesorge number.